A tree house in Tokyo: Reflections on Nikkei, citizenship, belonging, architecture, and art on the 75th anniversary of Japanese American and Japanese Canadian internment. Issue 2 (3rd July 2017) - Creighton, Millie
ABSTRACT: This think piece discusses the continuing influence of Japanese American and Japanese Canadian internment, which commenced 75 years ago in 1942 and also affected Nikkei from 13 Latin American countries. Contextualizing the Canadian case, the essay explores the lives of Raymond Moriyama, a Nikkei architect interned despite his Canadian birth and citizenship, and William Allister, a White Canadian Prisoner of War (POW) of Japan, and their mutual attempts to overcome bitterness through their architecture and art. The article explores the Canadian Embassy in Tokyo designed by Moriyama as a tree house, reflecting Moriyama's belief that a tree house is a special place where the human spirit can dwell and soar. The Canadian Embassy in Japan as a tree house proclaims possibilities of addressing historic wrongs and embracing diversity. North American Nikkei attempts to prevent further injustices against others are related to the contemporary context in which some North American voices advocate a registry of Arab Americans. The essay asserts that the official Redress acknowledgements by the United States and Canada in 1988 that the internment of people of Japanese descent was wrong stand as a precedent against such targeting of specific groups.